Africa’s Demographic Transition : Key Messages - Canning, David (World Bank, Washington, DC, 2016)
Declines in child mortality, followed by declines in fertility, produce a youth bulge generation and a period when a country has a large number of working age people and a smaller number of dependents. If gainfully employed, a large number of workers per capita gives a boost to the economy. The different demographic profiles, including stubbornly high fertility rates in a majority of Sub-Saharan African countries, make it urgent to act with targeted attention to country context and specific needs across a number of sectors. To reap a large demographic dividend, Africa requires policies that accelerate the reduction in child mortality and help couples to achieve a smaller family size, empower women and girls by improving their health, increasing investment in their education and skills, and providing them with greater market, social, and decision-making power. The size and duration of a dividend will also depend on job creation and improvements in domestic saving.